2019
DOI: 10.33988/auvfd.451328
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance profiles of vancomycin resistant enterococci in chicken meat samples

Abstract: Antibiotic resistance is one of the serious threats to global public health and food safety today. Acquired antibiotic resistance in microorganisms arises from prevalent use of antibiotics for human and animal medicine. Owing to the fact that Vancomycin Resistant Enteroccocci (VRE) is a vital problem for public health, determination of the antibiotic resistance profiles of Enterococcus spp. isolates have crucial importance as a part of the farm to fork food safety. In the study, 120 retail chicken meat samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…Among the 100 chicken meat samples, 27% were determined to be Enterococcus spp. positive, which is close to the value of 28.6% that was reported by Pesavento et al (2014) and the value of 30% that was reported by Onaran et al (2019). Yüksel et al (2013), Kilonzo-Nthenge et al (2015), Donado-Godoy et al (2015), Şentürk (2017), Kim et al (2018), andSanlibaba et al (2018) reported higher prevalence values of 43%, 82.2%, 94%, 91.66%, 77.7%, and 79.50%, respectively, while Bayram et al (2011) and Gousia et al (2015) reported lower prevalence values of 12.5% and 21.7%, respectively.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Among the 100 chicken meat samples, 27% were determined to be Enterococcus spp. positive, which is close to the value of 28.6% that was reported by Pesavento et al (2014) and the value of 30% that was reported by Onaran et al (2019). Yüksel et al (2013), Kilonzo-Nthenge et al (2015), Donado-Godoy et al (2015), Şentürk (2017), Kim et al (2018), andSanlibaba et al (2018) reported higher prevalence values of 43%, 82.2%, 94%, 91.66%, 77.7%, and 79.50%, respectively, while Bayram et al (2011) and Gousia et al (2015) reported lower prevalence values of 12.5% and 21.7%, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…The antibiotic sensitivity of the E. faecalis and E. faecium isolates differ depending on geographical conditions. Various studies have been conducted in Turkey (Kasimoglu-Dogru et al 2010, Onaran et al 2019Gökmen and Ektik, 2022), Canada (Aslam et al 2012), Amerika-Tennessee (Kilonzo-Nthenge et al 2015), Northwest Greece (Gousia et al 2015), Colombia (Donado-Godoy et al 2015), and South Korea (Kim et al 2018;Kim et al 2019). In the present study, 40.3% of the isolates were resistant to erythromycin and 71.64% of the isolates exhibited resistance to tetracycline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Absence of the vanA gene in phenotypically resistant isolates were in aggrement with several studies (Gousia et al, 2015;Raafat et al, 2016;El-Tawab et al, 2019;Onaran et al, 2019). In this context, Gousia et al (2015) in Greece found that eight out of 30 E. faecium and one E. faecalis vancomycin-resistant isolates did not harbour the vanA, Raafat et al (2016) reported that only one of the 10 vancomycin-resistant isolates was vanA-positive in foods of animal origin, El-Tawab et al (2019) reported that vanA was detected in three out of nine vancomycin-resistant strains isolated from milk and milk products in Egypt and in a recent study by Onaran et al (2019) with the absence of the vanA gene in 14 of 20 phenotypically positive VRE strains. Vancomycin resistance is known to be mediated by several van types as van A, van B, van C, van D, van E etc.…”
Section: Vancomycin Resistance and Vana Genesupporting
confidence: 66%
“…On the other hand, Rozanska et al (2015) reported moderate prevalence rate (49%) of Enterococcus spp. However, a very low prevalence rate of 30% was reported by Onaran et al (2019), which may be due to good hygienic practices followed in sampling.…”
Section: Isolation Of Enterococcus From Chicken Meatmentioning
confidence: 93%